STRATEGI MARKETING MIX PAKET HAJI DAN UMRAH DALAM MENINGKATKAN DAYA TARIK MASYARAKAT DI PT ABA TOUR AND TRAVEL KOTA SUKABUMI - Dikrilah Dikrilah; Amani Awalia Safitri (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Facing competition from haj and umroh travel agents at PT ABA Tour and Travel in Sukabumi City, implementing a marketing strategy concept that really understands strong management and can facilitate competition in buying interest in haj and umroh packages with the various advantages contained in these packages. This type of research is field research, with primary and secondary data sources. While the data collection techniques are observation, interviews, and documentation. The data analysis technique in this study is descriptive qualitative. The results of this study are that the marketing mix strategy used by PT. ABA Tour and Travel of Sukabumi City in increasing public attractiveness. By visiting the community directly to the field through recitations, attending events held by government and private agencies, through social media, making a friendly gesture between the alumni of the PT. ABA Tour and Travel Sukabumi City, and always prioritize service. The advantages are guaranteed facilities and services for Hajj and Umrah packages, Umrah packages have a high interest rate, have good business prospects, fourth, have a unique and attractive promotion strategy, fifth, after becoming alumni of the congregation, all of them are still entitled to become the sixth family of PT ABA Tour and Travel, always updates on Youtube and Instagram about activities both in the company and while worshiping Umrah. The drawbacks are incompetent human resources, promotional activities that are sometimes limited, ONH Plus Hajj Packages which are only known by a few levels of society, and social media, namely on Facebook, which doesn't work well (not updated)